BCL11B gene heterozygosity causes weight loss accompanied by increased energy consumption, but not defective adipogenesis, in mice. Issue 5 (4th May 2017) - Inoue, Jun; Ihara, Yusuke; Tsukamoto, Daisuke; Yasumoto, Keisuke; Hashidume, Tsutomu; Kamimura, Kenya; Hirano, Shigeki; Shimizu, Makoto; Kominami, Ryo; Sato, Ryuichiro
Abstract: BCL11B is a zinc finger-type transcription factor that regulates the development of the white adipose tissue (WAT), skin, central nervous system, and immune system. BCL11B is required for proper adipocyte differentiation, and BCL11B − / − embryos at E19.5 have very low amounts of the subcutaneous WAT. Here, we demonstrated that BCL11B + / − mice have lower body weight than BCL11B + / + mice, whereas the expression of adipogenic marker genes in the WAT was comparable between BCL11B + / + and BCL11B + / − mice. Histological analysis indicated that BCL11B + / − mice fed a high-fat diet have much smaller white adipocytes and lipid droplets in the WAT and liver, respectively. In addition, BCL11B + / − mice had increased energy consumption under both standard and high-fat diets. Thus, this study identifies BCL11B as a regulator of energy metabolism, and it is unlikely that BCL11B functions in the WAT contribute to energy metabolism in BCL11B + / − mice. Graphical abstract: : BCL11B+/− mice have much smaller white adipocytes in the WAT and much smaller lipid droplets in the liver under a high-fat diet.